Digital Intimacy and the Death of Presence: Rethinking Human Relations in Hyperconnected Societies - Daitey William (International Journal of Social Science, Education, Communication and Economics (SINOMICS Journal), 2025)
The rapid expansion of digital communication technologies has transformed the structure of human interaction within hyperconnected societies. This study examines the emergence of digital intimacy and its implications for the decline of authentic human presence in contemporary communication practices. Using a qualitative conceptual approach grounded in communication theory, media ecology, existential philosophy, and critical digital studies, this article explores how social media platforms, algorithmic systems, and virtual interaction reshape intimacy, identity, and relational experience. The findings reveal that hyperconnectivity produces a paradoxical condition in which individuals remain continuously connected yet increasingly experience emotional fragmentation, loneliness, performative communication, and communicative fatigue. The study introduces the concept of “presence erosion” to explain the weakening of embodied interaction and existential closeness caused by excessive technological mediation. Furthermore, the article argues that digital capitalism commodifies emotional expression and social interaction through engagement-driven communication systems that prioritize visibility over authenticity. Although digital technologies provide opportunities for global connectivity and social participation, they simultaneously threaten the depth of human relationships by replacing direct presence with symbolic and algorithmic interaction. This study contributes to global communication scholarship by offering an interdisciplinary theoretical framework for understanding the crisis of presence in digital civilization. Ultimately, the article emphasizes the importance of reconstructing communicative ethics grounded in empathy, attentiveness, and authentic human engagement within increasingly mediated social environments.